Optimalisasi Pemberian Bantuan Sosial Kepada Fakir Miskin pada Dinas Sosial, Pemberdayaan Perempuan dan Perlindungan Anak - Rudi Kurniawan; Takdir Takdir; Hadi Iskandar; Romi Asmara (Asia-Pacific Journal of Public Policy, 2020)
For the sake of implementing the handling of the poor to provide optimal, effective, and efficient social assistance, which is carried out by government agencies, it is necessary to evaluate appropriate recipients of this assistance. It is necessary to carry out a process of monitoring and evaluating recipients of social assistance who are not suitable to be a beneficiary in order to produce provision of targeted social assistance. This study aims to observe closely how to optimize the provision of social assistance to the poor at the Office of Social Affairs, Women's Empowerment and Child Protection in North Aceh Regency, Indonesia, and the obstacles or challenges encountered in its implementation. A qualitative approach was employed in the data collection process. The results of this study indicate that the social problems for the poor occurring in North Aceh Regency are increasingly complex and continue to develop. This condition requires the local Government to give priority to the implementation of social welfare in the field of handling the poor. This is relevant to the population and the complexity of social problems that exist in North Aceh District which tends to increase annually.